Front Cover: Conception and Evaluation of Fluorescent Phosphine‐Gold Complexes: From Synthesis to in vivo Investigations (ChemMedChem 11/2022). (7th June 2022) - Rousselle, Benjamin; Massot, Aurélie; Privat, Malorie; Dondaine, Lucile; Trommenschlager, Audrey; Bouyer, Florence; Bayardon, Jérôme; Ghiringhelli, François; Bettaieb, Ali; Goze, Christine; Paul, Catherine; Malacea‐Kabbara, Raluca; et al.
Abstract : The Front Cover shows the strategy for designing theranostic agents by highlighting some key criteria such as the therapeutic part, the probe, but also its biocompatibility, which includes in particular the water solubility of the compound. The combination of these aspects allows to maximize the chances of obtaining a good efficacy of theranostics in vivo. Cover design by Ewen Bodio. More information can be found in the Research Article by Benjamin Rousselle, Catherine Paul, Raluca Malacea‐Kabbara, Ewen Bodio et al.